Rethinking the Christian Studies Classroom: Reflections on the Dynamics of Teaching Religion in Southern Public Universities - Gravett, Sandie (Teaching theology and religion, 2011)
An extended set of conversations conducted by three religious studies faculty teaching at large public universities in the Southern United States spurred these reflections on how their institutional locations inflected issues such as the cultural expectations students bring to the classroom, how these expectations interact with the evolving priorities of religious studies departments, and how these factors affect the balance among the various subfields of religious studies and theology that make up such departments.